The internet of things and its impact on social relationships involving mutual trust - Kobayashi, Guiou; Broens, Mariana Claudia [UNESP]; Gonzalez, Maria Eunice Quilici [UNESP]; Quilici-Gonzalez, José Artur (Institute of Electrical and Electronics Engineers (IEEE), 2016)
In this paper, we investigate possible positive and negative consequences of the Internet of Things (IoT), characterized as the scenario in which computing-like technological devices and people can interact and exchange data without the need for deliberate human-to-human interaction, in social practices involving trust. Without denying the positive consequences of IoT, our interest is to discuss the following question: Might the rapid development of artificial autonomous systems, in the context of IoT, undermine the common sense notion of mutual trust? This question will be investigated using the concept of technological affordance, which extends the concept of affordance, according to which organisms directly perceive action opportunities (or affordances) in the environments in which they live because of their co-evolutionary long-term history. We consider that agent/environment interaction processes are predominantly self-organized, with organisms adjusting their actions in the world mainly through learning processes, without any omnipotent central controller. In the case of humans, collective social relationships involving mutual trust seem to result from direct self-organized interactions among members of social groups. Such direct collective interactions generate long-term social habits involving mutual trust that play a central role in human social identity. Nowadays, however, a great part of social interaction is mediated by technologies such as IoT. In this context, possible consequences of such indirect interactions are investigated, focusing on the hypothesis that significant changes in the sense of trust that supports human actions might be expected.
Keywords: Affordances; Collective habits; Internet of Things; Trust